Stability Demonstrating Validated High-Pressure Liquid Chromatographic Method for the Simultaneous Determination of Levodopa and Benserazide - Rayudu, Sunil; Manoranjani, Medikonda; Anitha, D (International Journal of Pharmaceutical Investigation, 2025)
Background An accurate, rapid, inexpensive, and straightforward, reliable simultaneous assay technique was developed and demonstrated to evaluate Levodopa and Benserazide using RP-HPLC. Materials and Methods The suggested approach achieved efficient chromatographic separation at a flow rate of 1 mL/min with a wavelength of 228 nm using a Luna phenyl hexyl column (250 mmx4.6 mm, 5 µ), acetonitrile and 0.1% formic acid as the mobile phase. Results and Discussion The retention time for Levodopa was 2.457 min, whereas that for Benserazide was 3.887 min. Isocratic chromatography was carried out in around six min at room temperature. Using a mathematical technique, we were able to determine that the system’s suitability parameters fall within reasonable bounds. In a linear analysis, stages with regression coefficients of 0.999 were used. The drug recovery rate was between 98%-102%, which is within acceptable range. Conclusion The method was determined to be appropriate for bulk and formulation analysis, and the validation findings were positive. In accordance with ICH recommendations, the suggested action is justified.
Keywords: Development; ICH guidelines; RP-HPLC; Validation